Study protocol for monitoring SARS-CoV-2 infection and its determinants in Catalonia (Spain): an observational and participatory research approach in a Sentinel Network of Schools. Issue 1 (25th January 2022) - Bordas, Anna; Soriano-Arandes, Antoni; Subirana, Maria; Malagrida, Rosina; Reyes-Urueña, Juliana Maria; Folch, Cinta; Soler-Palacin, Pere; Gascón, Mireia; Sunyer, Jordi; Anton, Andres; Blanco, Ignacio; Fernández-Morales, Jessica; et al.
Abstract : Introduction: Since the SARS-CoV-2 became of concern in January 2020, many preventive measures have been adopted in educational settings to ensure the control of COVID-19 pandemic among children and staff in schools. This study aims to set up a school sentinel surveillance network with the purpose of monitoring SARS-CoV-2 infection, seroprevalence as well as to analyse the impact of preventive interventions of SARS-CoV-2 in school settings. Additionally, we will assess diverse screening strategies in a cohort of students and school staff to monitor the screening acceptance and its potential impact. Altogether, we hope this study will enable the design of more effective strategies for the prevention of COVID-19 spread. Methods and analysis: The sentinel schools' study is a cross-sectional, school-based project including 26 participating sentinel schools in Catalonia (Spain). Children, adolescents and staff at the schools will be invited to participate. This project will be carried out from January 2021 to June 2022 as follows: (1) twice yearly serological testing and molecular SARS-CoV-2 detection and questionnaires covering SARS-CoV-2 symptoms, tests, health, knowledge, attitudes and behaviours; (2) an environmental evaluation carried out in different classrooms; (3) SARS-CoV-2 transmission dynamics and the impact of different variants among confirmed cases and classmates; (4) a participatory process by which the participants are invited to act as coinvestigators to evaluate prevention strategies and provide recommendations to improve COVID-19 prevention in schools. Descriptive analysis will be performed for the main variables collected. The incidence and seroprevalence will be calculated and the association with sociodemographic factors and school characteristics will be determined using multivariate logistic regression. Ethics and dissemination: Ethical approval was obtained from the IDIAPJGol and the Hospital Universitari Vall d'Hebron ethics committees. A report will be generated quarterly. Findings will be disseminated at national and international conferences and published in peer-reviewed journals.